Finite element and experimental analysis for the effect of elliptical chord shape on tubular T-joint strength - Hamed, A.F.; Khalid, Y.A.; Sahari, B.B.; Hamdan, M.M. (Professional Engineering Publishing, 2001)
The strength of T-tubular joints with elliptical and circular cross-section tube chords with circular cross-section tube braces has been investigated. Experimental tests to determine the joint strength of these T-joints subjected to tension, compression, in-plane bending and out-of-plane bending loading cases have been carried out. A rig has been designed and built for that purpose. Three types of T-joint connections, namely type 1, type 2 and type 3, were selected. In type 1, the joint consisted of braces welded perpendicularly to the circular chord outer diameter, while for type 2 the brace had been welded perpendicularly to the elliptical chord minor diameter and for type 3 the brace has been welded perpendicularly to the elliptical chord major diameter. The chord has been held as fixed-fixed for all types. The material used in all tubes tested was mild steel. Throughout this investigation the ultimate loads and ultimate moments obtained from the tests have been converted to non-dimensional strength values for fair comparisons. Finite element models for similar T-joints for the three types were created and used under the same loading cases. Shell elements have been used to model the mesh required. An elastic analysis has also been carried out. The experimental results obtained show that type 3 joints are stronger than type 1 for all the loading modes. The increase in load and moment varies from 12.16 to 27.27 per cent. On the other hand, type 2 joints were found to be weaker than type 1 joints by 7.5-27.68 per cent for different loading modes. A comparison between experimental results and finite element analysis has also been made. It shows a percentage variation of 0.89-34.40 per cent. Another comparison with existing tubular joint design formulae showed that these formulae are conservative and highly safe for the geometry used.